Use of ICT In Teaching Physics in Secondary Schools. - Ahebwa, Nelson (Kabale University, 2024)
Most secondary school educators face the challenge of developing and implementing technology in teaching and learning, the e-learning research project at Mwizi secondary school involves media-rich software to enable simulation and visualization of Concepts in physics. The objective of the project is to transform the way physics is taught in physical classrooms at Mwizi Secondary School to increase student's conceptualization and comprehensive understanding of physics and decrease failure rates in physics particularly in Electromagnetism. The approach is designed to help learners develop the best intuition about and conception models of Electromagnetism materials. The change is directed at the active methods of a collaborative hands-on environment with the use of Audio-visual lessons. Web-based assignments and individualized response system. The objective of the research is to examine the learning outcomes (LO) of Mwizi secondary school students who study Electromagnetism in physical classrooms and devise how the learning outcomes would be improved using online Methods. My study is to establish that e-learning has a significant and strong positive effect on the learning outcomes of Mwizi secondary school students. The e-learning will enable learners to change Electromagnetism materials from being abstract to being concrete.